IMPORTANCE PERFORMANCE ANALYSIS (IPA) APPLICATION FOR EXTERNAL EVALUATION OF PERFORMANCE ORGANISATION MISSION STATEMENT - Handiwibowo, Gogor Arif (Journal of Research and Technology, 2017)
One of formulation strategy result is organization’s mission statements. On implementation step, organization’s mission statements spread and implemented in organization activities. Evaluation step needed to describe the evaluation of all organization activities based on mission statements. Overall, evaluation step needed to ensure the alignment of formulation step until implementation step. The method of Importance Performance Analysis (IPA) is here proposed to evaluate the achievement of organization’s mission statements from the external perspective. This method is implemented at the evaluation in a part of mission statements at MMT – ITS Department from the students perspective. The evaluation is about to analyze the gap between importance and performance level of the mission statements.